Printed RFID systems for sustainable IoT: synergistic advances in conductive inks, antenna architectures, and scalable manufacturing - Wang, Xintai; Kuznetcov, Maksim; Jiang, Wenfeng; Tang, Zhongyu; Wei, Zhangchenyu; Zhang, Aili; Wei, Naixu; Li, Xiaoying (Frontiers in Electronics, 2025)
This review investigates the revolutionary potential of printed RFID technology in enabling next-generation IoT systems through sustainable manufacturing. The analysis systematically evaluates emerging conductive ink formulations, including metallic nanoparticles, carbon-based nanomaterials, MXenes, and hybrid composites, while assessing their performance trade-offs in electrical conductivity, environmental stability, and printing compatibility. Fundamental design strategies for high-performance antennas are examined, focusing on impedance matching optimization, radiation pattern control, and substrate-material synergy. Advances in printing methodologies such as inkjet deposition, screen printing, and direct ink writing are comparatively analyzed, with particular attention to the trade-off between performance and efficiency in high-resolution patterning versus industrial-scale production. Technical bottlenecks restricting commercial application are critically evaluated, emphasizing material property limitations and performance variations induced by the printing process. Finally, the study proposes three synergistic innovation pathways: intelligent material discovery through machine learning algorithms, multi-parameter simulation-guided antenna design, and hybrid manufacturing integrating multiple printing technologies. These integrated approaches aim to accelerate the transition from prototype development to industrial deployment of printed RFID systems. This comprehensive assessment provides actionable insights for advancing eco-friendly, mass-producible RFID solutions that meet the escalating demands of ubiquitous IoT connectivity across various smart environments.